Maritime Preference Of Students From Schools In Ciliwung Watershed - Rayuna Handawati; Nisrina; Bukhori Brata Kusuma; Renggo Tri Utomo; Elva Susanti Meylani (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2020)
This research aims to study maritime preference of students from schools in Ciliwung watershed. Maritime preference in a community pictures how a country could be depicted as a maritime country. The population in this research are 12th grader students that have been taught about Indonesia’s maritime potential in geography class from 29 schools located in Ciliwung watershed. The data was obtained through survey using questionnaire. The result shows that overall, the maritime preference from students have a weak tendencies in all aspects, including foods, fashion, travelling, daily behaviour, and professions/preference. Students whose schools located in the upstream part of the watershed have lower maritime preference compared to students from the middle and downstream area, even though they also have learned about maritime topic in school. The individual and family background affected their maritime preference and it could be said that the people who lived in the hinterland have a lesser preference of sea than the people who lived in a coastal area. Keywords: preferensi, maritime , geography